2006
DOI: 10.1002/ijc.22117
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of the APC promoter but lack of APC mutations in myxoid/round‐cell liposarcoma

Abstract: The adenomatous polyposis coli (APC) protein is a key component of the WNT signalling pathway wherein it acts as a scaffolding protein in controlling the level of the proto-oncoprotein b-catenin. Although APC has been shown to be genetically or epigenetically inactivated in a variety of carcinomas, little is known about its role in sarcoma. Liposarcomas (LPSs) are the second most common soft tissue sarcoma in adults. Despite different histology and malignancy, the myxoid and round-cell LPSs belong to one tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, they have demonstrated the presence of methylation of the APC promoter that induces a downregulation of the APC transcript [6]. …”
Section: Discussionmentioning
confidence: 99%
“…However, they have demonstrated the presence of methylation of the APC promoter that induces a downregulation of the APC transcript [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Haydon et al (36) have shown that cytoplasmic and nuclear accumulation of h-catenin occurred in osteosarcoma without any activating mutation. Sievers et al (37) reported that APC gene promoter was hypermethylated without mutations in myxoid liposarcoma. Protocols are in progress in our laboratory to obtain clinical specimens to determine whether down-regulation of secreted Wnt antagonists or APC by hypermethylation or deletion are responsible for enhanced Wnt activity in STSs.…”
Section: Discussionmentioning
confidence: 99%
“…This results in the transcriptional activation of Wnt-1 gene that leads to the development of lobuloalveolar hyperplasia and eventually cancer (2). Furthermore, epigenetic changes or mutation at any nodal point of the Wnt pathway also leads to the development of cancer (79)(80)(81). It is well established that dysregulation in components of the Wnt pathway are responsible for tumorigenesis, and among them, betacatenin/TCF component has been widely used in transgenic mouse model to elucidate and characterize canonical Wnt pathway.…”
Section: Animal Model Of Breast Cancer For Wnt Pathwaymentioning
confidence: 99%